Experimental Implementation of Hydraulic Turbine Dynamics and a Fractional Order Speed Governor Controller on a Small-Scale Power System - Claudia Sabrina Monteiro Da Silva; Nei Junior Farias Da Silva; Florindo A. De C. Ayres Junior; Renan Landau Paiva De Medeiros; Luiz Eduardo Sales E Silva; Vicente Ferreira De Lucena (IEEE Access, 2024)
In this paper, the practical application of automatic control techniques is performed to enhance the performance of the isochronous speed regulator of hydraulic turbines, thus making the electrical power system more efficient. To achieve this, the dynamic model of the 2kVA small-scale power system is employed for controller tuning. This system encompasses a synchronous generator and a coupled DC motor, with the hydraulic turbine dynamics incorporated into a microcontroller that replicates the behavior of larger power plants. For this purpose, a fractional-order PID controller (FOPID) is developed, given that this controller offers two additional degrees of freedom for design purposes. Therefore, in the design of the FOPID controller, a methodology based on analytical values of gain and phase margin is used. Additionally, a classical PID controller is tuned using the pole placement method to match the performance of both controllers. The aim of the study is to assess the effectiveness of the proposed methodology through comprehensive computational simulations and practical experimental tests, considering variations in the reference value and load, and qualitative analysis through temporal and quantitative analysis, using performance indices. The results demonstrate that the proposed methodology outperforms other approaches and confirms its effectiveness and flexibility. Thus, this article significantly contributes to the field of power generation system control, highlighting the importance of experimental validation to ensure performance in real-world scenarios.